Survey and analysis of effect of online teaching of "Military Epidemiology" course: based on the students' perspective - WU Na; XIANG Ying; YUAN Zhiquan; XIA Tingting; HU Qin; CHEN Zheng; CAI Tongjian; ZHANG Yao; LI Yafei; WU Shuxing; MA Xiangyu (Yixue xinzhi zazhi)
Objective Taking the course "Military Epidemiology" as an example to evaluate the effect of online teaching, and explore suitable online teaching methods for military medical colleges based on the students' perspective.Methods We conducted an anonymous questionnaire survey among the undergraduate students who participated in online teaching of “Military Epidemiology”. The content of questionnaire included online teaching effectiveness, challenges and advantages of online teaching, online teaching methods, assessment and evaluation of online teaching, and the application of online teaching in daily teaching. SPSS 20.0 software were used for statistical analysis.Results 235 students were included in the survey. The results demonstrated that most students were satisfied with the online teaching (89.4%). Most students believed that online and offline teaching had similar effects in terms of focused learning (51.1%), teacher-student interaction and communication (38.3%), course content understanding (61.7%), homework completion (61.7%), and classroom atmosphere (44.7%). Lack of awareness of self-directed learning was the biggest challenge faced by students in online teaching (62.6%). "Live + online communication " was the most favorite teaching method for students (33.6%). Stuck and delay were the main reasons for distraction (68.9%). Most students believed that taking a break after watching for 40 minutes was more conducive to concentration (69.8%). 49.4% of students believed that the final exam should still be the most important assessment content of online teaching. 47.7% of students believed that some courses could be taught online in the future.Conclusion Students generally have high satisfaction with the effectiveness of online teaching, but online teaching poses certain challenges to students. Strengthening online communication, classroom supervision, and optimizing related technologies will be beneficial for further improving the effectiveness of online teaching.